دور جودة الحياة الوظيفية في تنمية الولاء التنظيمي للعاملين في المؤسسة الاقتصادية-دراسة حالة مؤسسة سونلغاز فرع تقرت- - حكيمة, غوار; كريمة, حمدة; بوبكر, بن قلية; محمد الاخضر, حمي (جامعة الوادي - University of Eloued, 2023)
"ملخص: تهدفهذهالدراسةإلىإبرازدور جودةالحياةالوظيفيةبأبعادها(فرص الترقي والتقدم الوظيفي، أسلوب الإشراف، الأجور والمكافآت، الرضا الوظيفي، الاتصال والتواصل التنظيمي)في تنميةالولاء التنظيمي لدى العاملين بمؤسسة سونلغاز فرع تقرت،حيث يتكون مجتمع الدراسة المستهدفة من العاملين بالمؤسسة، وقدتمالاعتمادفيهذهالدارسةعلىالمنهجالوصفي التحليلي،واستخدام الاستبانةكوسيلةلجمعالبيانات اللازمة،حيث تم توزيع (100) استبانة وتم استرجاع (43) استبانة صالحة،ولمعالجةوتحليلهذهالبياناتتمالاعتمادعلىالبرنامجالإحصائي (SPSS). وتوصلتالدراسةإلىعدةنتائجأهمهاتوفرجودةالحياةالوظيفيةمنوجهنظرالعاملين بمؤسسة سونلغاز فرع تقرتبدرجة عالية،ووجودعلاقةذاتدلالةإحصائيةعندمستوىالدلالة(α≤ 0.05)بينأبعــادجــودةالحياةالوظيفيةومستوىالولاء التنظيمي،وتبينأيضاأنكلمنبعديفرص الترقي والتقدم الوظيفي،الرضا الوظيفي كانلهما تأثيرافعالاعلىمستوىالولاء التنظيميفيمؤسسةسونلغاز تقرت. "" This study aims to highlight the role of the quality of work life in its dimensions (opportunities for promotion and career progression, supervision style, wages and rewards, job satisfaction, communication and organizational communication) in developing organizational loyalty among employees of the Sonelgaz Foundation, Touggourtbranch, where the target study population consists of employees of the institution. In this study, the descriptive analytical approach was relied upon, and the questionnaire was used as a means for collecting the necessary data. (100) questionnaires were distributed and (43) valid ones were retrieved. To process and analyze this data, the statistical program (SPSS) was relied upon. The study reached several results, the most important of which is the availability of the quality of work life from the viewpoint of the employees of the Sonelgaz Corporation, Touggourtbranch, with a high degree, and the existence of a statistically significant relationship at the significance level (α ≤ 0.05) between the dimensions of the quality of work life and the level of organizational loyalty, and it was also shown that each of the two dimensions is opportunities Promotion, job advancement, and job satisfaction had an effective impact on the level of organizational loyalty in the Sonelgaz TouggourtFoundation. "
Keywords: جودة الحياة الوظيفية، ولاء تنظيمي، رضا وظيفي، عاملين، مؤسسة اقتصادية.; Keywords: quality of work life, organizational loyalty, job satisfaction, employees, economic institution.